2020
DOI: 10.3892/ol.2020.11429
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profile of cholangiocarcinomas in China

Abstract: Cholangiocarcinoma (CCA) is a primary malignancy, which is often diagnosed as locally advanced or metastatic. Previous studies have revealed genomic characteristics of CCA in Western patients, however comprehensive genomic features of CCA in Chinese patients have not been well understood. To explore the specific genomic characteristics of Chinese patients with CCA, a total of 66 patients with CCA, including 44 intrahepatic CCA (iCCA) and 22 extrahepatic CCA (exCCA) cases, were studied. The most commonly altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 74 publications
1
28
1
Order By: Relevance
“…All sequencing data were obtainedby using Illumina NextSeq 500 (Illumina, Inc., CA) in OrigiMed laboratory certified by College of American Pathologists (CAP) and Clinical Laboratory Improvement Amendments (CLIA). GAs were identified followed previous study 19 , 20 . Single nucleotide variants (SNVs) were identified by MuTect (v1.7).…”
Section: Methodsmentioning
confidence: 99%
“…All sequencing data were obtainedby using Illumina NextSeq 500 (Illumina, Inc., CA) in OrigiMed laboratory certified by College of American Pathologists (CAP) and Clinical Laboratory Improvement Amendments (CLIA). GAs were identified followed previous study 19 , 20 . Single nucleotide variants (SNVs) were identified by MuTect (v1.7).…”
Section: Methodsmentioning
confidence: 99%
“…They analyzed the frequency and type of genetic aberrations in detail by comprehensive genomic profiling, and found the genomic heterogeneity between eastern and western patients of iCCA, but the relationship between TMB and prognosis was not mentioned. Besides, Tian et al investigated the comprehensive genomic features of Chinese patients with iCCA, and explored the relationship between TMB and some gene alternations [35]. It should be noted that TMB of their cohort was more than that in our study.…”
Section: Tp53 Rbm10 Kras and Ipo5mentioning
confidence: 60%
“…Similarly, they observed specificities expressed in iCCA (STK11, CCND1, FGF19, FGF3, FGF4 and PBRM1). For FGFR2, they are expressed in both Western and Chinese cohorts [ 7 ]. Through the cBioPortal website [ 29 , 30 ], we merged six clinical cohorts to analyze their genetic alteration events, survival time and the proportion of several demographic factors ( Figure 1 ).…”
Section: Genomics Alterations and Epigenetic Changes In Ccamentioning
confidence: 99%
“…Analyzing the annual mortality rate of CCA, the average mortality rate for the period 2010–2014 was 0.3–2.88 (per 1 × 10 5 inhabitants) [ 6 ]. However, higher mortality rates (>4, per 1 × 10 5 inhabitants) including China [ 7 ], Japan [ 8 ], South Korea [ 9 ], Thailand [ 10 ], Taiwan [ 11 ] and Austria [ 12 ]. It has also been confirmed that men have a higher odds ratio than women [ 13 ].…”
Section: Introduction To Ccamentioning
confidence: 99%